Some Principles of Compensatory Action - Jr., E. Jay Howenstine (Quarterly Journal of Economics, 1946)
Some Principles of Compensatory Action Get access E. Jay Howenstine, Jr. E. Jay Howenstine, Jr. Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 61, Issue 1, November 1946, Pages 165–168, https://doi.org/10.2307/1882408 Published: 01 November 1946